2008
DOI: 10.1103/physrevlett.100.256102
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nanotips on the Hydrophilicity of Metallic Nanorod Surfaces

Abstract: The hydrophilicity of vertically aligned metal nanorods with sharp nanotips were investigated experimentally. Ruthenium and platinum nanorod arrays were deposited on flat silicon substrates using oblique angle sputter deposition. We show that the effects of nanotips on nanorods should be considered in the "hemiwicking" model for hydrophilic metallic samples. With the influence of nanotips, we successfully explained the experimental contact angles of water sessile drops on metallic nanorod surfaces. Our experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…It was found that the average contact angle of Pt nanorods was about 52 • , as shown in figure 4(a), indicating a hydrophilic surface. This value is comparable with the previously reported contact angle of Pt nanorods [23]. Similarly, for the normal angle deposited flat Teflon thin film, the average contact angle was about 108 • (see figure 4(b)), which indicates a hydrophobic surface, and it is in close agreement with the previously reported values of the contact angle of Teflon films [1,10].…”
Section: Contact Angle Measurements and Modelingsupporting
confidence: 92%
See 1 more Smart Citation
“…It was found that the average contact angle of Pt nanorods was about 52 • , as shown in figure 4(a), indicating a hydrophilic surface. This value is comparable with the previously reported contact angle of Pt nanorods [23]. Similarly, for the normal angle deposited flat Teflon thin film, the average contact angle was about 108 • (see figure 4(b)), which indicates a hydrophobic surface, and it is in close agreement with the previously reported values of the contact angle of Teflon films [1,10].…”
Section: Contact Angle Measurements and Modelingsupporting
confidence: 92%
“…Under the Cassie and Baxter assumption, the fluid forms a composite surface with the solid where the water droplet sits upon a composite surface of the solid tops and the air gaps, alternating between a fluid-solid interface and a fluid-vapor interface. Therefore, the Wenzel's model [23,24], which assumes that the fluid completely wets the solid structure, was modified by introducing the fractions f s and f a , which correspond to the area in contact with the liquid and the area in contact with the trapped air beneath the drop, respectively [24]:…”
Section: Contact Angle Measurements and Modelingmentioning
confidence: 99%
“…Although it is still a subject of controversy, it seems that a critical factor controlling nanocarpet formation is the penetration of the liquid into the inter-rod space of the 1D nanostructured surfaces. Although the literature on this subject has mainly focused on CNT arrays, its expected impact in biomedical research, superhydrophobicity and microfluidics has fostered the investigation of other systems such as OAD nanorods of Si [572][573][574], functionalized Si [575], SiO 2 [576,577], carbon [485], metal [578] and ZnO [563]. Indeed, the nanocarpet effect has already served to increase the WCA on 1D surfaces [563,573] through the formation of a double or hierarchical roughness.…”
Section: Nanocarpet Effectmentioning
confidence: 97%
“…As a result, individual nickel nanorod grown by our technique is a single crystal with facets, which is similar to the results reported previously. 32,35 The top-view and cross-sectional SEM images of the asprepared nickel nanorod arrays on silicon substrates are displayed in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%